Metamorphosis: The Dynamics of Symbolism in European Fairy Tales - Vaz da Silva, Francisco (2007)
Folklorists have become renowned for focusing on aspects of form and classification to the detriment of content and meaning. Metamorphosis: The Dynamics of Symbolism in European Fairy Tales seeks to reverse this tendency in showing, through an examination of the folkloric data, that European fairy tales involve complex symbolism. This book seeks to explain - in reference to the notion of metamorphosis - the puzzling contradictory attributes of fairy-tale figures that have discouraged the study of meanings in this field, and proposes that the workings of metamorphosis in fairy tales reveal a pervasive cyclic ontology that underlies mythology and ritual. The issue of universal symbolism is again examined - divested from any «archetypal» generalizations - as a subject of worthy reflection.